The Igbo-African Conceptualization of Death as a Journey and Not a Destination - Onwuatuegwu, Ignatius Nnaemeka (International Journal of Culture and History, 2024)
The issue of death has engaged many thinkers in almost every epoch or era. More so, different philosophers of various cultures have varied conceptions of death as well as rendering differing definitions and interpretations of the concept. Heidegger, for instance, sees man as a being destined to die and, therefore, man lives towards death. Death, simply put in that line of thought, therefore, is the primary purpose or destination of man on earth. This idea renders everything man does on earth as a venture in futility. Nevertheless, man is a being unto immortality. Death from the Igbo-African ontological point of view is but only a vehicle with which man is conveyed to immortality. It is an unavoidable path which every single individual person must unavoidably pass through if one is to be translated and transformed into immortality. The writer in the work resorted simply to the methodological approach of expository and philosophical reflection to accomplish the goal of the study. Invariably, the conclusion that death is, therefore, not a destination but a journey is drawn.